2013
DOI: 10.1017/s0021088900000437
|View full text |Cite
|
Sign up to set email alerts
|

Dr Lee's Collection of Cylinder Seals

Abstract: Dr Lee was known as a collector of cylinder seals only because six of them were published by Cullimore in 1843. Now twenty seals have been rediscovered in the Buckinghamshire County Museum in Aylesbury, and have been registered and recorded. Some of the preliminary drawings made for Cullimore's publication have also survived and have thrown light on the way the seals were recorded for publication in the early 1840s. Here a full catalogue and assessment of Lee's collection is presented, together with evidence f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Unprovenanced OSPS seals in European museums (1840-1914) 11 What follows are the collection histories of nine unprovenanced seals that form part of significant museum collections in Berlin, Geneva, Leiden and Paris formed in the nineteenth and early twentieth centuries (Porter 2001: 118-22). Very relevant to our understanding of practices that led to the formation of collections of this type is a study by Brett Thorn and Dominique Collon of a group of seals acquired by John Lee (1783-1866) and now in the Buckinghamshire County Museum (Thorn and Collon 2013). The authors have demonstrated that seal collecting had already gained popularity by the 1840s-in many cases by those with opportunities to travel within 2001: nos.…”
Section: Osps Seals Excavated Prior To 1945mentioning
confidence: 99%
“…Unprovenanced OSPS seals in European museums (1840-1914) 11 What follows are the collection histories of nine unprovenanced seals that form part of significant museum collections in Berlin, Geneva, Leiden and Paris formed in the nineteenth and early twentieth centuries (Porter 2001: 118-22). Very relevant to our understanding of practices that led to the formation of collections of this type is a study by Brett Thorn and Dominique Collon of a group of seals acquired by John Lee (1783-1866) and now in the Buckinghamshire County Museum (Thorn and Collon 2013). The authors have demonstrated that seal collecting had already gained popularity by the 1840s-in many cases by those with opportunities to travel within 2001: nos.…”
Section: Osps Seals Excavated Prior To 1945mentioning
confidence: 99%